Computers, Videos and Simulations during Brownian Motion Studies - Valdés Castro, R.; Tricio, V. (Revista Cubana de Física; Vol 24 No 1 (2007): IV Ibero-American Workshop on Teaching of University Physics, 2007)
Brownian motion is a phenomenon whose investigation was a key to advance of Physics and Chemistry in the beginnings of XX century. For experimental study of this phenomenon we have developed a set of activities. In our work we show a simple way to observe Brownian motion and for experimental verification of Einstein’s formula. To accomplishment measurements we use our software Análisis de Imágenes. We also described activity about simulation of Brownian motion and particles distribution.